Analysis of the handling of cases of sexual violence in terms of the National Police Chief Regulation Number 3 of 2008 - Arel Dewanta Bhara Prabowo (Police Studies Review, 2021)
Sexual violence is a problem that often occurs around us. Some of the victims of sexual violence do not want to report what happened to them and bury it more in themselves. The police, as law enforcers, have even played a role in dealing with acts of sexual violence by creating a particular implementation unit for women and children, namely the PPA Unit and the victim handling mechanism with Perkap No. 3 of 2008. Thus, this research explores how handling sexual violence acts based on Perkap No.3 of 2008. The preparation of this research uses a qualitative approach with the type of field research. Then to discuss how to handle sexual violence based on Perkap No. 3 of 2008 at Polres Metro South Jakarta, the researcher used an analysis knife of the A6 exceptional service theory, the theory of law enforcement effectiveness, and the concepts related to the focus of the problems that were formulated. This study can conclude that the handling of sexual violence at the South Jakarta Police in terms of the investigation flow mechanism is under Perkap No.3 of 2008. However, in services related to investigation facilities, it is still inadequate with the main factor that is still missing, namely the Special Service Room. In addition, several obstacles were found in handling sexual violence, namely internal and external factors. Based on the results of the research, there are several suggestions to the leadership of the South Jakarta Polres Metro; building a particular service room and completing the investigative support facilities and human resources for the PPA Polres Metro South Jakarta Unit.